Development and Evaluation of Technology Enhanced Interaction Framework Method for Designing Accessible Technologies for Visually Impaired People - Angkananon, Kewalin; Wald, Mike; Phetkeaw, Thimaporn (Frontiers in Computer Science, 2021)
This research developed and evaluated a software development support method to help non-expert developers evaluating or gathering requirements and designing or evaluating digital technology solutions to accessibility barriers people with visual impairment encounter. The Technology Enhanced Interaction Framework (TEIF) Visual Impairment (VI) Method was developed through literature review and interviews with 20 students with visual impairment, 10 adults with visual impairment and five accessibility experts. It is an extension of the Technology Enhanced Interaction Framework (TEIF) and its “HI-Method” that had been developed and validated and evaluated for hearing impairment and supports other methods by providing multiple-choice questions to help identify requirements, the answers to which help provide technology suggestions that support the design stage. Four accessibility experts and three developer experts reviewed and validated the TEIF VI-Method. It was experimentally evaluated by 18 developers using the TEIF VI-Method and another 18 developers using their preferred “Other Methods” to identify the requirements and solution to a scenario involving barriers for people with visual impairment. The “Other Methods” group were then shown the TEIF VI-Method and both groups were asked their opinions of its ease of use. The mean number of correctly selected requirements was significantly higher (p < 0.001) for developers using the TEIF VI-Method (X̄ = 8.83) than the Other Method (X̄ = 6.22). Developers using the TEIF VI-Method ranked technology solutions closer to the expert rankings than developers using Other Methods (p < 0.05). All developers found the TEIF VI-Method easy to follow. Developers could evaluate requirements and technology solutions to interaction problems involving people with visual impairment using the TEIF VI-Method better than existing Other Methods. Developers could benefit from using the TEIF VI-Method when developing technology solutions to interaction problems faced by people with visual impairment.